PENGARUH DESKRIPSI PEKERJAAN DAN PENEMPATAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN KONTRAK DI PERUMDA TIRTA HIDAYAH KOTA BENGKULU - Rorinsandika, Rorinsandika; Islamuddin, Islamuddin (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
The problem of research is that Perumda Tirta Hidayah often faces various challenges in managing human resources, especially in terms of managing contract employees. Contract employees at Perumda Tirta Hidayah are often faced with different work situations than permanent employees, both in terms of job stability and opportunities for development. The purpose of the study was to determine the effect of job description and job placement on the job satisfaction of contract employees in the Tirta Hidayah Regional Public Company, Bengkulu City. This research can be classified as causal associative quantitative research, the respondents are all contract employees of Perumda Tirta Hidayah Bengkulu City totaling 75 people. Data collection was done using questionnaires, data analysis was carried out statistically descriptive and multiple linear regression models. The results of the study show that job descriptions have an effect on the job satisfaction of contract employees, where a good job description will increase the job satisfaction of contract employees. Then job placement affects the job satisfaction of contract employees, where appropriate placement will increase employee job satisfaction. Furthermore, job descriptions and job placement affect the job satisfaction of contract employees. This explains that when job descriptions and job placements are well designed and implemented, they both have a positive impact on employee satisfaction levels. Keywords: Job Description, Job Placement, Job Satisfaction